2021
DOI: 10.1111/are.15671
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation withBacillusspecies improves growth, intestinal histomorphology, innate immunity, antioxidative status and expression of growth and appetite‐regulating genes of Nile tilapia fingerlings

Abstract: This study assessed the impact of dietary supplementation of single-and multi-strain Bacillus-based probiotics on growth performance, intestinal morphometry, blood parameters, immune-oxidative status and transcriptomic response of Nile tilapia for 60 days. Fish (N = 150, 1.632 ± 0.035 g) were allocated into five experimental groups:(1) Control group (CG) that was fed on a basal diet; (2) Eco. 0.01%, received basal diet with 0.1 g/kg Ecobiol; (3) Eco. 0.02%, received basal diet with 0.2 g/kg Ecobiol;(4) Pro-F F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 83 publications
2
17
0
Order By: Relevance
“…Previous studies also reported a significant effect of Bacillus spp. on growth, disease resistance, and hematological parameters of Nile tilapia (Soltan et al 2016;Sutthi et al 2018;Elsabagh et al 2018;Kuebutornye et al 2020;Won et al 2020;Ghalwash et al 2021) and other aquatic species (Hauville et al 2016;Munir et al 2016;da Paixão et al 2017;Kong et al 2017;Wang et al 2017;Amoah et al 2021;Saravanan et al 2021). In this present study, the effect of two previously isolated Bacillus spp.…”
Section: Introductionmentioning
confidence: 47%
“…Previous studies also reported a significant effect of Bacillus spp. on growth, disease resistance, and hematological parameters of Nile tilapia (Soltan et al 2016;Sutthi et al 2018;Elsabagh et al 2018;Kuebutornye et al 2020;Won et al 2020;Ghalwash et al 2021) and other aquatic species (Hauville et al 2016;Munir et al 2016;da Paixão et al 2017;Kong et al 2017;Wang et al 2017;Amoah et al 2021;Saravanan et al 2021). In this present study, the effect of two previously isolated Bacillus spp.…”
Section: Introductionmentioning
confidence: 47%
“…Death specificity was detected using re‐isolation of S. iniae pathogen from freshly dead fish for two weeks (the length of the post challenge observation period), mortalities were monitored, and the relative level of protection (RLP) was performed according to the rules of Diab et al, 2021; Newman and Majnarich (1982). Liver samples were also collected after 24 hours post challenge from each triplicate after the fish were previously anaesthetized with clove oil, then liver samples were instantly shocked in a liquid nitrogen, and stored at −80°C for further RNA extraction (Ghalwash et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the specificity of the PCR products, dissociation curve analyses were performed. A geometric average of two tilapia reference genes (β-actin and UBCE) was used to standardize quantitative RT-PCR data (Ghalwash et al, 2022).…”
Section: Cdna Synthesis and Quantitative Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations